Fe(III) and S0 reduction by Pelobacter carbinolicus. - Lovley, D R (1995)
There is a close phylogenetic relationship between Pelobacter species and members of the genera Desulfuromonas and Geobacter, and yet there has been a perplexing lack of physiological similarities. Pelobacter species have been considered to have a fermentative metabolism. In contrast, Desulfuromonas and Geobacter species have a respiratory metabolism with Fe(III) serving as the common terminal electron acceptor in all species. However, the ability of Pelobacter species to reduce Fe(III) had not been previously evaluated. When a culture of Pelobacter carbinolicus that had grown by fermentation of 2,3-butanediol was inoculated into the same medium supplemented with Fe(III), the Fe(III) was reduced. There was less accumulation of ethanol and more production of acetate in the presence of Fe(III). P. carbinolicus grew with ethanol as the sole electron donor and Fe(III) as the sole electron acceptor. Ethanol was metabolized to acetate. Growth was also possible on Fe(III) with the oxidation of propanol to propionate or butanol to butyrate if acetate was provided as a carbon source. P. carbinolicus appears capable of conserving energy to support growth from Fe(III) respiration as it also grew with H2 or formate as the electron donor and Fe(III) as the electron acceptor. Once adapted to Fe(III) reduction, P. carbinolicus could also grow on ethanol or H2 with S0 as the electron acceptor. P. carbinolicus did not contain detectable concentrations of the c-type cytochromes that previous studies have suggested are involved in electron transport to Fe(III) in other organisms that conserve energy to support growth from Fe(III) reduction.(ABSTRACT TRUNCATED AT 250 WORDS)